the The Influence Of Students' Reading Interest On Indonesian Language Learning Achievement In Pakel I State Primary Schools - Widiyaningsih, Nunuk; Sudigdo, Anang; Santosa, Wijaya Heru (Universitas Sarjanawiyata Tamansiswa, 2024)
The author observed that interest in reading among Pakel I State Elementary School students is very low. This is based on observations made when the author carried out observations throughout the time at SD Negeri Pakel I . The aims of this research are (1) to prove the influence of reading interest on student learning achievement, (2) to describe the influence of reading interest on student learning achievement. This research is qualitative and quantitative research using development methods or Research and Development (R&D). The instruments used were interviews, questionnaires and observations. The research subjects were students in grades 4, 5 and 6 of Pakel I State Elementary School, totaling 31 students. The author observed that interest in reading among Pakel I State Elementary School students is very lowThis research methodology is based on the development model of Borg & Gall (2003: 775). The development procedure used in this research consists of 10 stages, namely: (a) research and data collection, (b) planning, (c) development of the initial form of the product, (d) initial field trials, (e) product revision, (f ) field trials, (g) operational product revisions, (h) operational field trials, (i) final product revisions, and (j) dissemination. The results of this research are (1) the results of the Kolmogrov-Smirnov normality test show that the value obtained is 0.104 ≥ 0.05) so that the data is normally distributed, the homogeneity test results show a result of 0.621 in the range of 0.60-0.799 or interest in reading with learning achievement has strong relationship. Meanwhile, the t test results show results of 0.722 and 0.046 < 0.05 or it can be concluded that H0 is rejected and Ha is accepted. (2) Thus, the research conclusion is that there is a significant difference between the average student learning outcomes before and after literacy. So that interest in reading has a significant effect in increasing the learning achievement of students in grades 4, 5 and 6 at Pakel I State Elementary School.